Metabolic profile of liver damage in non-cirrhotic virus C and autoimmune hepatitis: A proton decoupled 31P-MRS study. Issue 90 (May 2017) - Hakkarainen, Antti; Puustinen, Lauri; Kivisaari, Reetta; Boyd, Sonja; Nieminen, Urpo; Arkkila, Perttu; Lundbom, Nina
Highlights: 31 P-MRS is more sensitive in detecting inflammation than fibrosis in the liver. 31 P-MRS has stronger correlations with liver function tests than histology. 31 P-MRS may be useful to recognize patients with ongoing fibrogenesis. Abstract: Purpose: To study liver 31 P MRS, histology, transient elastography, and liver function tests in patients with virus C hepatitis (HCV) or autoimmune hepatitis (AIH) to test the hypothesis that 31 P MR metabolic profile of these diseases differ. Materials and methods: 25 patients with HCV (n = 12) or AIH (n = 13) underwent proton decoupled 31 P MRS spectroscopy performed on a 3.0 T MR imager. Intensities of phosphomonoesters (PME) of phosphoethanolamine (PE) and phosphocholine (PC), phosphodiesters (PDE) of glycerophosphoethanolamine (GPE) and glycerophosphocholine (GPC), and γ, α and β resonances of adenosine triphosphate (ATP), and nicotinamide adenine dinucleotide phosphate (NADPH) were determined. Liver stiffness was measured by transient elastography. Inflammation and fibrosis were staged according to METAVIR from biopsy samples. Activities of alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALT) and thromboplastin time (TT) were determined from serum samples. Results: PME had a stronger correlation with AST (z = 1.73, p = 0.04) and ALT (z = 1.77, p = 0.04) in HCV than in AIH patients. PME, PME/PDE, PE/GPE correlated positively and PDE negatively with inflammatory activity. PE, PC and PME correlated positively with liver function tests. Conclusion: 31 P-MRS suggests a more serious liver damage in HCV than in AIH with similar histopathological findings. 31 P-MRS is more sensitive in detecting inflammation than fibrosis in the liver.